Milícias in Rio de Janeiro: deconstructing the myth of a violent everyday peace through a feminist perspective - Gouveia Junior, Luis (Frontiers in Political Science, 2024)
Milícias have proliferated across Brazil, engaging in criminal activities while maintaining close connections to the Brazilian state and politicians. They seek political validation by presenting themselves as combating drug traffickers and reducing violence, positioning peace and security as fundamental to their political appeal. Therefore, examining the role of peace within these criminal organizations through the lens of peace and conflict studies provides valuable insights into how Brazilian militias work. Through an analysis of the rhetoric used by politicians, the media, and residents in areas under milícias’ control, it becomes apparent that these criminal groups assert their role in establishing a form of “everyday peace.” However, this form of peace is inherently violent, resulting in a paradoxical concept of ‘violent everyday peace.’ Consequently, the feminist framework’s emphasis on the public/private distinction and the continuum of violence becomes crucial in addressing this paradox. By applying this feminist concept, it becomes evident that milícias generate a limited sense of peace in the public sphere while perpetuating violence in the private domain. Private violence, however, is often overlooked by those unaffected by milícia control, allowing these groups to garner political support. These findings enrich the study of criminal organizations in Brazil and the concept of everyday peace, which has not been previously explored in the context of Brazilian milícias.